Regulating Inductive Reasoning in Sexual Assault Cases - Tanovich, David M. (To ensure that justice is done: essays in memory of Marc Rosenberg, 2017)
"This volume brings together leading scholars, practitioners, and jurists who have written chapters in tribute to the Honourable Marc Rosenberg's legal and ethical contributions to the administration of justice. Inspired by his work as a teacher, a lawyer, and a judge, the contributors reflect on key trends and contemporary issues in jurisprudence, legal education, the administration of justice, and legal ethics. The contributors examine topics including wrongful convictions, social justice and the criminal law, the role of the judge and lawyer, challenges facing the law of evidence, the past and future of Charter justice, and the function of legal education in contributing to the administration of justice in Canada and abroad. The book is, thus, both a tribute to the life, work, and contributions of Marc Rosenberg, and an indispensable resource for all those concerned with the ways in which we seek justice in and through the law."
Keywords: David Tanovich